Geological Age Data of the Ross Orogeny in the Terra Nova Intrusive Complex, Northern Victoria Land, Antarctica - Sang-Bong Yi; Mi Jung Lee (Geo Data)
This study aims to establish the timing of the formation of the Terra Nova Intrusive Complex (TNIC), located in Terra Nova Bay, northern Victoria Land, Antarctica. The TNIC is paleogeographically situated inland of the Wilson Terrane of northern Victoria Land and was formed during the Paleozoic Ross Orogeny. This study obtained and compiled sensitive high-resolution ion microprobe zircon U-Pb ages for five intrusive bodies in the south-central part of the TNIC. The results clarify the formation age (about 530-470 Ma) of the TNIC and the interrelationships among the various intrusive units, especially those in the south-central region. The Confusion Intrusive Unit was emplaced at 520-515 Ma. The Russell Gabbro intruded into the Confusion Intrusive Unit at 501±3 Ma. Approximately at the same time (about 500 Ma), the Vegetation Intrusive Unit formed, followed by the Abbott Intrusive Unit at about 485 Ma. These findings provide valuable data for interpreting the geological development of the Antarctic Continent and the evolutionary history of the Ross Orogeny.